Rancang Bangun Sistem Informasi Penjualan Batik Berbasis E-Commerce - Sunarti - AMIK BSI Jakarta (Universitas Bina Sarana Informatika, 2015)
Abstract The development of computer technology is very influential in terms of business. For the moment everything can be found in the intenet, is no exception with an online trading system called e-commerce. In this study made sales website batik-Based E-Commerce. The purpose of this website is to create a website sales and information about batik. Where this website is equipped with a sales transaction system that is practical as well as provide information about batik fairly complete, this website was made using the programming language PHP (Hypertext prepecessor) and MySQL for databases and assisted by the editors for web designing is Adobe Dreamweaver CS4. Data collection methods using secondary data obtained from the web and literature review. The method of system development information system using waterfall method, describe the functional model and ERD (Entity Relationship Diagram) to describe the data model. The purpose of this study was to determine the ease Provides information about the types of produk Batik is up to date and provide information so that the growing variety of batik batik knowledge of areas. With the built website can assist consumers in making purchases online that can be done anywhere and anytime. Keywords: Information Systems, Batik, E-commerce.